Isolasi Antosianin Kulit Terong Ungu (Solanum melongena) sebagai Biosensor Pendeteksi Kandungan Bahan Kimia pada Makanan - Ahmad Aris Arifin; Sucika Armiani; Herdiyana Fitriani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Anthocyanin is one of the color pigments natural plant. One source of anthocyanin is purple eggplant, production in West Nusa Tenggara reached 62.408 tons in 2020. Generally, purple eggplant is only used as a source of food, even though the skin has great potential for research development. Therefore, this study aims to maximize the utilization of purple eggplant skin by innovating to develop a food safety testing biosensor. This type of research is true experiment researche using a qualitative approach, and using a Completely Randomized Design (CRD) consisting of 10 treatments and 3 replications. The parameter observed was the color change on whatmann paper no 42 before and after being dripped with the tested chemical solution. Data analysis using Spectrophotometer test and chemical selectivity test. The results showed that of the 5 types of chemicals tested, sodium nitrite had the most obvious color change when reacted with purple eggplant skin anthocyanins, at a concentration of 5% before being dropped it was light brownish in color, after dripping it was yellowish orange, and dark orange at a concentration of 10%. So from these results indicate that anthocyanins purple eggplant skin potential to be developed as a biosensor natural for food safety testing, particularly in detecting the use of sodium nitrite to exceed the threshold for processed meat products.